Long-Term Impact of Coronary Artery Disease in Lung Transplantation - Ragalie, William S; Oliveira, Nilto C de; Cornwell, Richard; Meyer, Keith; Maloney, James D (Journal of Cardiology and Cardiovascular Medicine, 2019)
Background: Adoption of the Lung Allocation Score (LAS) has led to increased listing of older patients and those with idiopathic pulmonary fibrosis (IPF) for lung transplantation (LTX). Older patients and those with IPF have higher prevalence of coronary artery disease (CAD), a relative contraindication for LTX. The impact of the LAS on CAD prevalence and cardiovascular morbidity in LTX recipients is unknown. Methods: Retrospective review of single institution database from January 2000 to December 2010. Patients with and without CAD were compared by age, gender, LAS, single vs double LTX, and transplant indication. Survival was calculated by Kaplan-Meier method, and statistical significance determined by log-rank method. Survival analysis was performed on all patients and by 3:1 propensity matching. Differences in CAD, gender, and indication were determined by Chi-squared test. Differences in LAS and age were calculated with a two-tailed t - test. Results: In the pre-LAS era, 6.2% (9/145) recipients had CAD vs. 9.2% (17/184) in the post-LAS era (p = 0.411). Among all patients, recipients with CAD had a worse long term survival as estimated by Kaplan-Meier method (p = 0.001), although there was no statistically significant difference after propensity matching ((p = 0.14). Although more recipients in the post-LAS era had a diagnosis of IPF [15/145 vs. 71/184 patients, (p < 0.001)], there was no difference in the prevalence of CAD in the IPF cohort compared to others. There were no differences in cardiovascular deaths among recipients with CAD, with IPF, or in the post-LAS era. Patients with a pre-transplant diagnosis of CAD had an descreased risk of new onset postoperative atrial fibrillation (AF) (p = 0.007; HR:0.133; CI:0.030-0.583). Conclusion: Adoption of the LAS was not associated with a significant change in proportion of recipients with CAD who underwent LTX at our institution, despite an increase in recipients with IPF. Recipients with CAD had a higher risk of developing new postoperative AF and worse survival than patients without CAD. Differences in survival, however, could not be attributed directly to CAD based on propensity matched analysis.